2011
DOI: 10.1371/journal.pone.0017174
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Plasmodium falciparum Erythrocytic Cycle Induced by Angiotensin Peptides

Abstract: Plasmodium falciparum causes the most serious complications of malaria and is a public health problem worldwide with over 2 million deaths each year. The erythrocyte invasion mechanisms by Plasmodium sp. have been well described, however the physiological aspects involving host components in this process are still poorly understood. Here, we provide evidence for the role of renin-angiotensin system (RAS) components in reducing erythrocyte invasion by P. falciparum. Angiotensin II (Ang II) reduced erythrocyte i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 37 publications
5
58
0
Order By: Relevance
“…In this regard it is of interest that angiotensin-II has recently been shown to reduce erythrocyte invasion in vitro by P. falciparum in a dosedependent manner, and that the deletion allele of the ACE insertion/deletion polymorphism, which is associated with higher plasma ACE activity, has been reported to be protective against cerebral malaria (Dhangadamajhi et al, 2010;Saraiva et al, 2011). Further research into the question of whether the major genetic effects on plasma ACE activity at the ACE and ABO loci contribute significantly to differential susceptibility to severe malaria would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard it is of interest that angiotensin-II has recently been shown to reduce erythrocyte invasion in vitro by P. falciparum in a dosedependent manner, and that the deletion allele of the ACE insertion/deletion polymorphism, which is associated with higher plasma ACE activity, has been reported to be protective against cerebral malaria (Dhangadamajhi et al, 2010;Saraiva et al, 2011). Further research into the question of whether the major genetic effects on plasma ACE activity at the ACE and ABO loci contribute significantly to differential susceptibility to severe malaria would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four hours after treatment all peptides were able to reduce new ring formation at 10 −8 M concentration, which was studied by Saraiva et al as the ideal concentration for these inhibition assays (Saraiva et al, 2011). The tests were carried out in duplicate and a total of ten experiments were performed (n = 10).…”
Section: Effect Of the Ang II Ala Scan Analogs In The P Falciparum Ementioning
confidence: 99%
“…Saraiva et al have described studies that aimed at identifying the molecular mechanisms induced by Ang II, which are involved in the modulation of P. falciparum erythrocytic cycle. The results showed that Ang II have had some influence in the parasite ring forms reduction (47%) (Saraiva et al, 2011). Silva et al tested Alascan Ang II analogs to verify the importance of each residue of the Ang II native molecule and the intra and intermolecular peptide interactions with P. gallinaceum sporozoites.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II cannot be used as an antimalarial drug due to its vasoconstrictor effect [1,2]. Ten peptides related to it were synthesized by Fmoc solid phase strategy, purified by RP-HPLC, characterized by LC/ESI-MS and tested against mature Plasmodium gallinaceum sporozoites and Plasmodium falciparum early throphozoites.…”
Section: Introductionmentioning
confidence: 99%